Relative survival of patients with supratentorial low-grade gliomas - Smoll, Nicolas R. (Oxford University Press, 2012)
We sought to assess the population-based estimates of age-standardized survival among patients with low-grade gliomas (LGG) and to determine the impact of age and time on relative survival (RS). Data from the Surveillance, Epidemiology, and End Results (SEER) program of NCI from 1973 through 2006 were analyzed to assess survival among 5037 patients. Relationships were modeled using Dickman's piecewise constant hazards RS model. The 3- and 10-year age-standardized RS were 67% and 37%, respectively. When analyzed by age group, the 10-year overall survival (OS) and RS for children (age, <16 years), young adults (age, 16–39 years), adults (age, 40–64 years), and older patients (age, ≥65 years) were 86% and 86%, 61% and 62%, 40% and 43%, and 10% and 14%, respectively. The observed difference between OS and RS was larger among older patients (4%) and smallest among children (<1%). Older patients were 30.5 times (excess hazard ratio [eHR]; 95% confidence interval [CI], 20.3–50.0) as likely as young adults to die during the first year and 18.2 times as likely to die during the second year. Adults were 5.3 (eHR; 95% CI, 3.5–8.1) times as likely to die during their first year as young adults. In the remaining years, the observed survival differences were substantially decreased, and the presence of an age-by-follow-up interaction was observed. Survival among older patients with LGG was substantially different from the one computed for young adults and children. Despite the hazards across age groups not being proportional, RS does not provide additional information, compared with OS, in patients with LGG.